Improving the performance of LoRaWAN IoT system - Yapar, Gökçer. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
One of the technologies developed in LPWAN according to the IoT concept is the LoRaWAN protocol. This protocol works together with LoRa modulation. So far, studies on this protocol included only uplink communication. Moreover, the performance of the pure ALOHA type MAC protocol used in this protocol was not fully observed. Recently, investigations, including downlink communication, have revealed that the pure ALOHA type MAC protocol and downlink traffic have a negative impact on network scaling. A solution is provided to minimize these negative e ects in the LoRaWAN protocol. This solution is a scheduling method for synchronizing the gateway with the end devices. In addition, the proposed solution provides two different methods of sending aggregated acknowledgment messages, which are sent to the last devices from the gateway. This proposed solution has been observed to reduce downlink traffic when it is run with various test scenarios and to increase the capacity of the last device to which a gateway can serve. In other words, the proposed solution had a positive contribution to LoRaWAN scaling.
Keywords: Internet of things.